Early Management of Malaria in the Context of Elimination: Observations from Chitwan Medical College, Nepal - Lamsal, Daya Ram; Mirdamadi, Shirin (Journal of Chitwan Medical College, 2019)
Background: Nepal is entering a malaria elimination phase with the target for no indigenous cases set for 2025. The elimination phase is known to be a challenge due to knowledge and skills reduction as cases become rarer.Methods: We audited all malaria parasitology tests in Chitwan Medical College from January 2017 to December 2018. Slide positive rate, case treatment and timings were identified from case note review.Results: Over the 2 years, 1455 malaria tests were performed, 12 were positive, making the positive test rate at 0.83%. Eleven of these 12 case files were found. They were reviewed to find the case details. All cases were >16 years old. Four cases had P. falciparum, six cases had P. vivax,and in one case, the species was not identified. Four of the 12 cases fulfilled criteria for severe malaria. All P. falciparum cases had travelled outside Nepal in the past year. Median time from symptom onset to treatment was 170 hours. Median time from attendance to anti-malarial treatment was 9 hours. Three cases did not receive guideline antibiotics according to Nepal National Protocol.Conclusions: In conclusion, immediate testing with malaria RDT in all febrile patients presenting to CMC for early diagnosis and prompt treatment is recommended. In addition, we urge to inform colleagues on the features of severe malaria and the national treatment protocol including use of Primaquine for progressing to elimination target.